Studi Kapasitas Dan Tingkat Pelayanan Jalan: (Studi Kasus Jalan Mr. Muhammad Hasan Kota Banda Aceh) - Sriana, Tety; Hayati, Kemala (University of Muhammadiyah Aceh, 2021)
Mr. Muhammad Hasan is street one of the entrance gates to Banda Aceh City. The condition of the road is in steady condition, with a two-lane, two-way type divided with a median of 1.5 m wide. The role of this road is very strategic, considering that if a tsunami occurs, this road is one of the community's escaped roads. The results of initial observations of this road are still in a comfortable condition to drive, but it is necessary to research the level of service to anticipate its role as an escape road. Based on that, we want to know how the level of service on Jalan Mr. Muhammad Hasan. The purpose of this study was to determine the level of service Jalan Mr. Muhammad Hasan using the 1997 MKJI method. Data were collected through a survey of traffic volume and speed for 3 (three) days, namely Thursday, Friday and Sunday. The duration of the survey is 07.00-18.00 with 8 (eight) surveyors. The traffic volume is multiplied by the number emp, so we get the amount of flow at peak hours in the morning, afternoon and evening. The result of recording speed in m/second is converted to km/hour. Furthermore, the capacity of city roads, free flow speed and degree of saturation is calculated. Based on the value of capacity, speed and degree of saturation, the value of road service level is obtained. Based on the calculation results, the highest peak hours on observation day occurred in the afternoon, namely Thursday at 15.45-16.45 (2144 p.m./hour), Friday at 16.15-17.15 (2295 p.m./hour) and Sunday at 17.00-18.00 as many as 1698 smp/hour. hour. The capacity of the road on the three observation days was 6178 pcu/hour and the speed was 53.01 km/hour. The lowest degree of saturation occurred on Sunday afternoon at 0.18 and the highest occurred on Friday at 0.54 and overall it was still below 0.75 so there was no need for a scenario. The level of service in the morning and afternoon (Thursday, Friday, Sunday) still shows a value of A, while on Monday afternoon it becomes C and on Friday and Sunday it slightly decreases to B.